Redesign of Pneumatic Piston Using Design for Manufacture and Assembly (DFMA) Technique - Mustofa . (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2010)
Design for Manufacture and Assembly (DFMA) technique has been utilized intensively in industry for many years in order to increase the quality, decrease the cost and shorten the cycle time of a product. This paper is a detail application of the technique in the pneumatic piston product. The redesign effeciency of the product increases significantly from 25.9% to 67.45%. Keywords: manufacture and assembly